Analysis of Stream Function in a Powell-Eyring Fluid Flow with Couple-Stress Effect and Rotation - Ghazi, Rana; Zeki Hummady, Liqaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The effect of couple stress, slip condition, changing rotation, and other variables on the peristaltic flow of Powell-Eyring fluid in an inclined asymmetric channel with an inclining magnetic field through a porous media is investigated in this study. Constitutive equations obeying the Powell-Eyring fluid model are employed. In flow analysis, assumptions such as a low Reynolds number and a long wavelength approximation are used. The stream function and mechanical efficiency have closed form expressions devised. The stream function is expressed mathematically. Through the collection of figures, the impact of various criteria is explained and graphically represented Through the collection of figures, the impact has been explained of the Hartman number (Ha), the Darcy number (Da), the inclination of the magnetic field (β), the rotation (Ω), the porous medium parameter (w), the amplitude ratio (ϕ), the slip condition (β_1 ), and couple stress parameter (α) on stream function have been explained and graphically represented by using the perturbation method which is analytic method. These numerical results were achieved using the mathematical application MATHEMATICA.